Traumatic injuries to the ureter - Gayol-Collette, Mario; Viola-Peluffo, Julio C (Cirugía del Uruguay, 1973)
Out of 59 reno-ureteral traumatisms registered in the University Hospital (Hospital de Clínicas), we find two cases of ureteral traumatic lesions, one of which was due to a bullet wound, and the other, in our understanding the most serious, was an internal traumatism. The paper describes their clinical aspects and refers to the value of urographic studies in deterning the lesion. However this method should be completed by ascending pyelography. Pathogenesis and treatment are considered and the author includes a review of authors who have referred to this type of lesion.